Adsorption and photocatalytic degradation of benzene compounds on acidic F-TiO2/SiO2 catalyst. (May 2020) - Qiu, Lu; Li, Hanliang; Dai, Fangwei; Ouyang, Feng; Pang, Dandan; Wang, Hongjie
Abstract: The adsorption and photocatalytic degradation performance of F-TiO2 /SiO2 catalyst towards a series of benzene compounds were studied. The results revealed that the F-TiO2 /SiO2 catalyst is superior to TiO2 P25 in adsorption capacity and photocatalytic degradation under simulant sunlight irradiation. The adsorptive capacity for chlorobenzene is the highest and the degradation rate is the greatest among these target pollutants. The increase of absorptive organic molecules on acidic F-TiO2 /SiO2 catalyst benefits photocatalytic degradation. The photocatalytic reaction accords to Langmuir-Hinshelwood mechanism. The FTIR results indicated that the promoting effect of acidic centers on adsorption of benzene compounds depends on electron property of the functional groups. The electron-donating groups (–OH and –NH2 ) of benzene compounds are weakly adsorbed on acidic centers of the catalyst due to the competitive adsorption with H2 O, while the electron-withdrawing groups (–Cl and –NO2 ) are adsorbed more strongly at acidic sites. The monosubstituted chlorobenzene prefers to perpendicular adsorption on acidic surface, while the disubstituted benzenes prefer to horizontal adsorption, which decreases the adsorbed amounts. A photocatalytic rate mainly depends on electron donating property of the functional group and amount of adsorptive organic molecules, but not on electron density of benzene ring. Graphical abstract: Image 1 Highlights: F–TiO2 /SiO2 is superior in adsorption and photocatalytic degradation of organics. Increase of adsorptive amounts benefits photocatalytic degradation of benzene series. The electron-withdrawing groups are adsorbed strongly at acidic sites. Reaction rate depends on electron donating property of functional groups.